2021
DOI: 10.3389/fpls.2021.667351
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescent Xanthomonas hortorum pv. gardneri as a Tool to Quantify Bacteria in Planta, Screen Germplasm, and Identify Infection Routes on Leaf Surfaces

Abstract: Imaging technology can provide insight into biological processes governing plant-pathogen interactions. We created and used a bioluminescent strain of Xanthomonas hortorum pv. gardneri (Xgb) to quantify infection processes in plants using tomato as a model. An X. hortorum pv. gardneri is one of the four Xanthomonas species that causes bacterial spots in tomatoes. We used Xgb to quantify bacterial growth in planta, to assess disease severity in resistant and susceptible tomato lines, and to observe infection ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Healthy hydathodes have been reported to host a rich microbial community (Perrin et al, 1972). Several vascular bacterial pathogens of the Xanthomonas and Clavibacter genera have evolved to colonize this niche and can infect hydathodes (Lewis and Goodman, 1966; Carlton et al, 1998; Hugouvieux et al, 1998; Cerutti et al, 2017; Bernal et al, 2021; Mullens and Jamann, 2021). In contrast to stomata, hydathode pores seem unable to fully close and may thus facilitate pathogen entry and infection (Cerutti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Healthy hydathodes have been reported to host a rich microbial community (Perrin et al, 1972). Several vascular bacterial pathogens of the Xanthomonas and Clavibacter genera have evolved to colonize this niche and can infect hydathodes (Lewis and Goodman, 1966; Carlton et al, 1998; Hugouvieux et al, 1998; Cerutti et al, 2017; Bernal et al, 2021; Mullens and Jamann, 2021). In contrast to stomata, hydathode pores seem unable to fully close and may thus facilitate pathogen entry and infection (Cerutti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While X. hortorum pv. gardneri is not known to colonize vascular tissues, Bernal et al (2021) recently showed colonization of hydathodes upon inoculation of tomato plants with X. hortorum pv. gardneri.…”
Section: Resultsmentioning
confidence: 99%
“…Attempts to quantify the bacterial luminescence signal have relied on using luminometers to measure photon emission by bacteria that colonize a single leaf or plant (22). In some cases, the image processing software ImageJ is used to obtain numerical data from images obtained with ultra-sensitive CCD cameras (21,28).…”
Section: Introductionmentioning
confidence: 99%